MODIFIKASI ALAT PENCABUT PAKU PADA DINDING BANGUNAN - Zulkarnain Fatoni (Universitas Tridinanti Palembang, 2018)
Nails are hard pointed metal, generally made of steel, used to attach two materials by penetrating both. Nails are generally blown on materials using a hammer or nail gun that is driven by compressed air or a small explosive impulse. Attachment by spikes occurs in the presence of friction forces in the vertical direction and force of force in the lateral direction. The tip of the nail is sometimes bent to prevent the spikes coming out. One of the purposes of making this tool is as an alternative tool that has been used only to open the axle, bearing and the other but can be used to remove the spikes with little modification. From the results of the discussion and can be the force of the tensile rod on the spikes F = 4.5 kg), shear stresses that occur in the shaft thread (tg=0,542 kg/cm2), Initial shear Stress (tg=30,5 kg/cm2), yield bend that occurs in the rotary lever (sb=42,993 kg/cm2). then the modification of the nail-pulling device on the wall of the building can be used properly. Keywords: Nails, Lateral Directions, Yield